MAKNA SYUKUR DALAM QS. SABA` [34]: 13: ANALISIS TEMATIK DAN KONTRIBUSINYA TERHADAP PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Mubarak, Amien; Iskandar; Yusuf Qardlawi, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the meaning of gratitude (shukr) from a Quranic perspective, focusing specifically on QS. Saba’ [34]:13, which emphasizes that only a few servants attain the degree of ash-shakūr. The frequent reduction of gratitude to mere verbal expression necessitates a more comprehensive conceptual reorientation, particularly within the context of character education. This research aims to elucidate the dimensions of gratitude comprising the heart, tongue, and physical action and formulate its contribution to primary education. Employing the thematic exegesis (tafsir maudhu’i) method with an interdisciplinary approach, this study compares classical (Tafsir al-Jalalayn) and contemporary (Tafsir Tahlili by the Ministry of Religious Affairs RI) interpretations. The results indicate that: (1) gratitude in the Qur'an is a multidimensional ethico-spiritual concept encompassing cognitive, affective, and praxis dimensions; (2) the phrase “wa qalīlun min ‘ibādiya ash-shakūr” serves as a theological indicator that gratitude requires behavioral transformation; (3) the indicators of gratitude demand the integration of internal awareness, verbal articulation, and an orientation toward righteous deeds; and (4) these values contribute to the formulation of character education in elementary schools through the "Integrative Gratitude" model. This model establishes discipline, social empathy, and academic productivity as success indicators for students' gratitude. Thus, gratitude is not merely a verbal expression but a life paradigm that integrates spiritual consciousness with concrete action within the educational ecosystem.